Review and outlook: from single nanoparticles to self-assembled monolayers and granular GMR sensors - Weddemann, Alexander; Ennen, Inga; Regtmeier, Anna; Albon, Camelia; Wolff, Annalena; Eckstädt, Katrin; Mill, Nadine; Peter, Michael K.-H.; Mattay, Jochen; Plattner, Carolin; Sewald, Norbert; Hütten, Andreas (Beilstein Journal of Nanotechnology, 2010)
This paper highlights recent advances in synthesis, self-assembly and sensing applications of monodisperse magnetic Co and Co-alloyed nanoparticles. A brief introduction to solution phase synthesis techniques as well as the magnetic properties and aspects of the self-assembly process of nanoparticles will be given with the emphasis placed on selected applications, before recent developments of particles in sensor devices are outlined. Here, the paper focuses on the fabrication of granular magnetoresistive sensors by the employment of particles themselves as sensing layers. The role of interparticle interactions is discussed.
Keywords: bottom-up particle synthesis; dipolar particle coupling; granular giant magnetoresistance sensor; magnetic nanoparticles; self-assembly